Communication Patterns of Tourism Awareness Groups (Pokdarwis) in the Dusun Tlocor Community: Pola Komunikasi Kelompok Sadar Wisata (Pokdarwis) Pada Masyarakat Dusun Tlocor - Andrian, Denta Yoga; Rochmaniah, Ainur (Indonesian Journal of Public Policy Review, 2023)
This scientific article explores the communication patterns within the Sadar Wisata (Pokdarwis) group in Dusun Tlocor, Sidoarjo District, which was formed by the local government to develop tourism potential, particularly the emerging Pulau Lusi (Lumpur Sidoarjo). Using a qualitative descriptive approach, data was collected through informant interviews. The study reveals that the communication pattern within Pokdarwis exhibits a linear or continuous/chain communication style. The findings shed light on the dynamics of communication strategies employed by the group, enabling a deeper understanding of their efforts in developing tourism. These insights hold implications for fostering community participation and maximizing the economic benefits of tourism in the region. Highlights: Communication patterns: The study investigates the communication patterns within the Pokdarwis group in Dusun Tlocor, shedding light on how information and ideas flow among members and contribute to tourism development. Tourism development: The research focuses on the efforts made by the Pokdarwis group in developing tourism potential in Dusun Tlocor, highlighting the importance of effective communication strategies in attracting visitors and generating economic benefits. Community participation: The study emphasizes the significance of involving the local community in tourism development, as the formation of Pokdarwis demonstrates a collaborative approach to engage and empower residents in shaping the future of their region through effective communication. Keywords: Pokdarwis, communication patterns, tourism development, Dusun Tlocor, Sidoarjo District